Peran Guru Menciptakan Disiplin Kelas Terhadap Peningkatan Prestasi Belajar Siswa MI Muhammadiyah 11 Blimbing Paciran Lamongan - Zainal Mahfud (Jurnal Pendidikan Islam, 2019)
Abstract: The research focus discussed in this thesis is (1) How is the role of teacher in creating classroom discipline in MI Muhammadiyah 11 Blimbing Paciran Lamongan, (2) How is student achievement in MI Muhammadiyah 11 Blimbing Paciran Lamongan, (3) Is there any correlation between role teachers in creating classroom discipline with student achievement in MI Muhammadiyah 11 Blimbing Paciran Lamongan. This research uses the following methods: population, sample, data source, data collection method and also data analysis technique. In this research, it can be concluded that there are four roles that must be done by a teacher in creating classroom discipline, that is teacher as first implementer of discipline, teacher as student director in carrying out all school rules, teacher as supervisor in implementing all school rules and teacher giving gifts and punishments to the students. Student achievement of MI Muhammadiyah 11 Blimbing Paciran Lamongan in academic year 2014/2015 shows enough value. There is a correlation between the role of teachers in creating classroom discipline to improve student achievement in MI Muhammadiyah 11 TPAY Blimbing Paciran Lamongan and the correlation shown is quite correlation with score value of 0.698.